Students' Perception of 'Pidgin English' as a Medium of Instruction in Akinyele Local Government Area of Oyo State, Nigeria (2023)
This study assessed students' perception of 'Pidgin English' (PE) as a medium of instruction in Akinyele Local Government Area of Oyo State, Nigeria particularly in the context of multi-ethnic enclave prevalent in local government area. The study was prompted because this has not been explored by previous studies which had focused on the use of Nigerian Pidgin English by students while neglecting their perception and attitude to PE as medium of communication. The mixed methods design (qualitative and quantitative) was adopted because it allowed for data triangulation. Simple random sampling was used in selecting 10 schools in Akinyele LGA and 30 students from each Students' perception (r= 0.72) and Attitude (r=0.74) to PE scales as well as Interview Guide were used for data collection. Findings revealed that students had positive perception of pidgin English (x̄ = 2.89;2,5); also, there is positive attitude to pidgin English (x̄ = 2.98; 2.5). Based on these findings, it is therefore recommended that Nigerian Pidgin English should be allowed as medium of instruction.